2011
DOI: 10.1186/2040-2392-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of autoantibodies to GABAergic neurons in the central nervous system produced by a subset of children with autism

Abstract: BackgroundAutism is a neurodevelopmental disorder characterized by impairments in social interaction and deficits in verbal and nonverbal communication, together with the presence of repetitive behaviors or a limited repertoire of activities and interests. The causes of autism are currently unclear. In a previous study, we determined that 21% of children with autism have plasma autoantibodies that are immunoreactive with a population of neurons in the cerebellum that appear to be Golgi cells, which are GABAerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 78 publications
(83 reference statements)
0
34
0
Order By: Relevance
“…The former bind several different cell types in the cerebral and cerebellar cortex, hippocampus, amygdala and striatum (Wills et al, 2011). Reactivity against a 52 kDa autoantibody, later more accurately identified as the 45 kDa Ab analysed here, was primarily detected in calbindin-positive Golgi interneurons located in the Purkinje cell layer of the cerebellar cortex (Wills et al, 2007, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former bind several different cell types in the cerebral and cerebellar cortex, hippocampus, amygdala and striatum (Wills et al, 2011). Reactivity against a 52 kDa autoantibody, later more accurately identified as the 45 kDa Ab analysed here, was primarily detected in calbindin-positive Golgi interneurons located in the Purkinje cell layer of the cerebellar cortex (Wills et al, 2007, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These autoantibodies, displaying a significantly lower prevalence in population controls compared to autistic individuals (Wills et al, 2009; Goines et al, 2011), seemingly target different brain regions, including thalamus, hypothalamus, caudate nucleus, cerebral cortex, and putamen, but most consistently the cerebellum (Cabanlit et al, 2007; Wills et al, 2007, 2011). Cerebellar specific IgG autoantibodies, initially estimated approximately 52 kDa in size and directed mainly against calretinin-positive GABAergic Golgi cells, were identified by Western Blot analysis in plasma from children with ASD (Cabanlit et al, 2007; Wills et al, 2011). Histopathological and brain imaging studies have unveiled multiple abnormalities in the cerebellum of many autistic individuals, including a significant reduction in Purkinje cell number, cytoarchitectonic abnormalities and cytoplasmic inclusions in the deep cerebellar nuclei, and vermal hypoplasia (Fatemi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in burst structure are likely to affect the information transfer gated by the inhibitory feedback projections exerted by RTN neurons on the thalamic relay cells. The outcome of this alteration could affect the transthalamic corticortical connectivity (Gollo et al 2010;Paz et al 2011;Sherman and Guillery 2011;Theyel et al 2010;Villa et al 1999) such to generate an impaired processing of the information associated to psychiatric disorders (Ferrarelli et al 2010;Gogolla et al 2009;Lawrence et al 2010;Pinault 2011;Reynolds et al 2001;Wills et al 2011). …”
Section: Functional Connectivity Of Rtn Neurons Is Unchanged In Pvko mentioning
confidence: 99%
“…Later on, the same sera cohort was studied by IHC using the rostro-caudal extent of macaque brain. A specific subgroup of GABAergic interneurons located in the V1 layer was identified as the specific target [194]. Controversially, another study suggested that this staining might be unspecific because immunoreactivity was detected using serum of both healthy controls and a ASD patient with the intriguing fact that the IgG seropositive ASD patients presented more severe behavior and emotional problems compared to the IgG seronegative ones [195].…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%